Constatación de filoxera galicola (Dactylosphaera Vitifoliae Shimer) en Mendoza - Zuluaga, Enrique Mario (1963)
Although it cannot be discarded that the apparition of galicolous forms or phyloxera in Our zone might be an accidental phenomenon caused by special elimatic conditions, it seems nevertheless possible, according to our olEervations, that it is the result of the propagatiun of a race Of philoxera: the Dactylosphaera vitifoli.i vitifolii. At the Km. 8 Experimental Station of the Agricultural Institute of the vince (Instituto Provincial Agropecuario), the atlack of the radicolous phyloxea was proved on three american hvbriti rootstocks in a collection of 15 grafted plants, the affected plants being.